2009
DOI: 10.1017/s1751731109004169
|View full text |Cite
|
Sign up to set email alerts
|

The effects of allowance and frequency of allocation of deferred herbage, and grass silage feed value, when offered to ewes in mid-gestation on ewe and lamb performance and subsequent herbage yield

Abstract: The effects of (i) herbage allowance, (ii) frequency of allocation and (iii) grass silage feed value on ewe and lamb performance were studied in mid-gestation ewes. Furthermore, the effects of (i) herbage allowance, (ii) frequency of allocation and (iii) grazing date and their interactions on subsequent herbage yield and feed value were also evaluated. Swards, which had a cut of silage removed on 6 September, received fertiliser nitrogen (34 kg/ha) for extended (deferred) grazing between 6 December and 1 Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
4
10
3
Order By: Relevance
“…This structural characteristic of massai guineagrass followed the same trend of the leaf component (Figures 1(C) and (D)), which is more important than the stem. The relative diminution of the availability of leaves affects the animal intake and consequently its performance [13] [14].…”
Section: Resultsmentioning
confidence: 99%
“…This structural characteristic of massai guineagrass followed the same trend of the leaf component (Figures 1(C) and (D)), which is more important than the stem. The relative diminution of the availability of leaves affects the animal intake and consequently its performance [13] [14].…”
Section: Resultsmentioning
confidence: 99%
“…During extended grazing, allocation of herbage, by erecting and moving fences, is labour demanding and currently labour is an expensive commodity on many sheep farms. Previous studies at this centre (Keady and Hanrahan, 2009b,c) have shown that allocating herbage either daily or twice weekly did not alter animal performance or subsequent herbage growth.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies at this centre have shown that providing extended (deferred, winter) grazing for ewes in mid (Flanagan, 2003; Keady et al. , 2007; Keady and Hanrahan, 2009b), late (Keady et al. , 2007) or throughout (Keady et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations